PENGUJIAN COGNITIVE ABSORPTION TERHADAP KEPERCAYAAN-KEPERCAYAAN PENGGUNA UNTUK BERBAGI INFORMASI DI LINGKUNGAN VIRTUAL WORLDS - Supardi, Supardi (Jurnal Riset Akuntansi dan Keuangan, 2014)
Virtual Worlds (VWs) are media-rich  cognitively  engaging technologies that geographically dispersed organizations  can use  as a cost effective workplace collaboration tool. Using  a sharing  information in virtual worlds environment, the aims of this study is to investigate cognitive absorption within individual beliefs about the technology of virtual worlds use. Cognitive absorption, theorized as being exhibited through the five dimensions of temporal dissociation, focused immersion, heightened enjoyment, control, and curiosity, is posited to be a proximal antecedent of two important beliefs about technology use: perceived usefulness and perceived ease of use. A model, based on Bandura's Social Cognitive Theory, was developed to test number of variables as the antecedents of cognitive absorption, which include social factor and individual like familiarity and personal innovativeness.A sample of 218 respondents participated in the research. In informing the results, the study utilized the partial least square model with the support for SmartPLS 2.0 software. Our findings suggest that beliefs about VWs usage can be influenced by cognitive absorption. Significant relationships were found between familiarity and cognitive absorption, and between personal innovativeness and cognitive absorption. Theoretical and practical implications are offered.